2020
DOI: 10.1002/jgm.3161
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy related gene expression status in patients diagnosed with azoospermia: A cross‐sectional study

Abstract: Background Autophagy affects various aspects of the male reproductive system. Any defects in this process may lead to azoospermia. However, the exact molecular mechanisms of the autophagy pathway have remained largely obscure. Therefore, the present study aimed to investigate levels of autophagy pathway gene expression (i.e. Lc3B, Beclin1, ATG5 and Bcl2) in azoospermic patients. Methods The levels of Lc3B, Beclin1, ATG5 and Bcl2 mRNA expression in azoospermic patients and fertile males were evaluated by a real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Autophagy is involved in many physiological processes, including spermiogenesis and acrosome formation 26 . Studies have highlighted the importance of different ATGs in male fertility 28 , 29 . For instance, ATG5 and ATG7-mediated autophagy were shown to play a role in differentiation and cytoplasmic reduction of the flagellated motile sperm 29 , while Huang et al presented that ATG5 is required for elongating spermatid development, sperm individualization, and normal fertility in male mice 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is involved in many physiological processes, including spermiogenesis and acrosome formation 26 . Studies have highlighted the importance of different ATGs in male fertility 28 , 29 . For instance, ATG5 and ATG7-mediated autophagy were shown to play a role in differentiation and cytoplasmic reduction of the flagellated motile sperm 29 , while Huang et al presented that ATG5 is required for elongating spermatid development, sperm individualization, and normal fertility in male mice 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Beclin1 is the earliest key regulator in the study of autophagy. It binds to ligands and regulates the formation of autophagosome membranes and regulates intracellular autophagy activity ( Asgari et al, 2020 ). LC3 is located in the inner membrane of autophagic vesicles, and its expression product LC3 is activated along with the process of autophagy, and combines with phosphatidylethanolamine to form membrane type LC3-II.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that any change in gene expression can alter the physiological activity of the cell 14 . Today, a scientific link among miR and the prognosis of various human cancers has been proven in various studies.…”
Section: Discussionmentioning
confidence: 99%